Machiavellian character mediate the effect of locus of control in auditor dysfunction behavior - Nadi, I Made Putra Partha; Suputra, I D. G. Dharma; Wirajaya, I Gede Ary; Sari, Maria M. Ratna (International research journal of management, IT and social sciences, 2020)
This study aims to examine the character of Machiavellian in mediating the effect of locus of control on auditor dysfunctional behavior. This research was conducted by survey method through the distribution of questionnaires to auditors who work in public accounting firms in the province of Bali. The study population used in this study were all auditors working on KAP with a purposive sampling method. The number of samples acting as respondents amounted to 43 auditors, then the data obtained were analyzed by path analysis in SPSS. Based on the results of data analysis shows that the external locus of control and Machiavellian trait have a positive effect on the auditor dysfunctional behavior. This study also proves that Machiavellian trait variables mediate the influence of external locus of control on auditor dysfunctional behavior.